Investigation of yb-1 gene expression by syber-green based real-time pcr in brain tumor - Muhammad Redzwan, Sidik (Universiti Sains Malaysia, 2008)
Cancer generally is a genetic disease that can cause alteration in specific gene in which a group of cells display uncontrolled growth, invasion and metastasis. YB-1 Gene Y -box binding protein (YB-1) is a member of the cold-shock domain (CSD) protein superfamily and involved in many cellular functions, including transcriptional regulation, translational regulation, DNA repair, drug resistance and stress responses to extracellular signals. YB-1 gene can be found in a cytoplasm and nuclear cell. The YB-1 gene comprises 8 exons spanning 19 kb of genomic DNA and is located on chromosome I p34. The aim of the study is to differential relatively quantitative the expression of YB-I gene in brain tumor sample (meningioma) and normal brain sample (Astrocyte SVG I2). SYBR-Green I based Real-Time PCR was performed and data analysis using formula 2-MCt has demonstrated that YB-1 gene was over-expressed by 2.86 fold in comparison to its expression in normal sample. This preliminary data is very important in the future experiment for expression of YB-I gene showed the potential as a biology marker for detection of brain tumor.